Age and Gender Motivating Differences of Slovak Workers - Weberova, Dagmar; Hitka, MiloÅ¡; Lizbetinova, Lenka (International Review of Management and Marketing, 2017)
Work motivation depends not only on the sector of employment but also on factors such as age and gender. Today women play an important role in employment and their participation in economic life is constantly increasing. Performance incentives such as financial income, freedom, career advancement, challenges, opportunities of self-realization, and so on are more significant for men. Research of motivational differences by gender is based on the concept of fundamental differences between men and women, so on the existence of gender stereotypes which can be seen in a historical context. This is similar with age too. Younger adults are more motivated by a desire to increase profits and older adults are more motivated to retain what they already have. Based on their experience, older employees wish that their opinions are more respected while younger employees wish to be listened to. In this article, the impact of gender and age on employee motivation in Slovak companies is discussed. It has been concluded that there are significant differences based on gender at Slovak employees. This is reflected in 18 motivational factors. Furthermore, it has been pointed out to the fact that, considering age categories, there are also significant differences particularly at motivational factors such as basic salary, job security and fair employee evaluation. Keywords: Employee Motivation, Duncan Test, Motivation and Gender, Motivation and Age JEL Classification: M12